Peningkatan Keterampilan Menulis Teks Biografi Siswa Kelas X-10 di SMA N 8 Semarang dengan Pendekatan Culturally Responsive Teaching (CRT) - Efiyana, Nurul; Agus Wismanto,; Tutik Naviatun, (Prosiding Seminar Nasional Pendidikan Profesi Guru, 2024)
ABSTRACT This study aims to improve the biography writing skills of students in class X-10 at SMA N 8 Semarang using a Culturally Responsive Teaching (CRT) approach. CRT emphasizes the importance of considering students' cultural backgrounds in the learning process to enhance learning outcomes. This research employs a classroom action research design with cycles of planning, implementation, observation, and reflection. The participants were students who had difficulties in writing biographical texts. The intervention involved applying teaching strategies that are sensitive to local cultures and students' personal experiences, including the use of biographical examples of local figures and writing activities relevant to their cultural context. The results indicate a significant improvement in students' biography writing skills. Students made progress in text structure, appropriate language use, and the ability to connect biographical information with their cultural backgrounds. The study concludes that the CRT approach is effective in enhancing biography writing skills by making learning more relevant and meaningful for students. These findings are expected to contribute to the development of more inclusive and culturally responsive teaching strategies. Keywords: writing skills, biography texts, culturally responsive teaching, CRT, language education.